Data-driven analysis of the effect of screening and treatment on the spread of HIV in developing and developed countries - Abbas, Wasim; Masud, M. A.; Parveen, Sajida; Lee, Hyojung; Kim, Sangil (Frontiers in Public Health, 2024)
Introduction In this study, we used a mathematical epidemic model to explore the status of the HIV epidemic in the USA and Pakistan. In addition to studying the dynamics of the model, we fitted the model with recent data to estimate the parameters describing the epidemic in both countries. Results Our estimation shows that in the USA, the reproduction number is 0.9688 (0.9684, 0.9694); if the reproduction number is maintained at this level, it would take a long time to eradicate HIV entirely. Meanwhile, it is 2.2599 (2.2556, 2.2656) in Pakistan, which is due to a lack of awareness in the confirmed group and a lower rate of maintained treatment. We also estimated the rate of vertical transmission, which plays a significant role in Pakistan but not in the USA. Discussion We conclude that improving the screening rate and educating people would be effective for controlling HIV in Pakistan, whereas improved screening rate in the USA can eradicate HIV faster.